Influence of Home Factors on At-Risk Learners’ Academic Performance in Limpopo Province, South Africa - Letsoalo, M. E; Maoto, R. S; Chuene, K. M (Journal of Gender, Information & Development in Africa, 2018)
This exploratory study followed a qualitative phenomenological design. It explored the influence of home factors on the academic performance of at-risk learners in South Africa’s Limpopo Province. The authors used secondary data from a parent study that sought to determine how dysfunctional families hamper effective learning in primary schools in South Africa’s Limpopo Province. Though participants in the parent study included both learners and teachers, this paper reports on findings from ten purposively identified learners from two primary schools in the rural area of Ga Modjadji. Polkinghorne’s (1995) analysis of narratives was used to reformulate data from participants using both Bronfenbrenner’s (2005) ecological theory and Maslow’s (1943) theory of human motivation as paradigmatic lenses. This study concludes that the academic performance of at-risk learners is influenced by multiple factors within their micro- and meso-systems. The home circumstances of at-risk learners appear to be detrimental to meaningful learning. Family dysfunction has a significant negative effect on the performance of learners and, ultimately, on the well-being of children. This study recommends that the Department of Basic Education should sensitise parents to the need for, and importance of, support, as well as provide education interventions for at-risk learners. The department should also provide rehabilitative programmes so that at-risk learners may improve in their performance. Finally, the Department of Social Development should make every effort to ensure that the affected learners have stable care and adequate social support.
Article published in the Journal of Gender, Information & Development in Africa Volume 7 Number 3, Dec. 2018 Pp 97-12
Keywords: Dysfunctional Family; Learners’ Perspective; Academic Performance; Home Factors; At-Risk Learners; Academic achievement; Dysfunctional families-Evaluation